2023
DOI: 10.3390/nu15020284
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Betaine Supplementation Mitigates Maternal High Fat Diet-Induced NAFLD in Offspring Mice through Gut Microbiota

Abstract: Maternal betaine supplementation has been proven to alleviate non-alcoholic fatty liver disease (NAFLD) in offspring caused by maternal high-fat diet (MHFD). The gut–liver axis plays an important role in NAFLD pathogenesis. However, whether maternal betaine supplementation can alleviate NAFLD in offspring by the gut–liver axis is unknown. C57BL/6J mice were fed with high-fat diet for 4 weeks before mating, and supplemented with 1% betaine during pregnancy and lactation. After weaning, offspring mice were fed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…The putative mechanisms underlying the effects of betaine on lipid metabolism included changes in gut microbiota (i.e., reductions in Intestinimonas, Acetatifactor, and Desulfovibrio, and increases in Lachnoclostridium and Romboutsia), with intergenerational metabolic impacts [49]. In addition, maternal betaine supplementation has been shown to reduce hepatic triglyceride content in offspring mice by decreasing the relative abundances of Proteobateria, Desulfovibrio, and Ruminococcus, but increasing Bacteroides and Parabacteroides [50]. In addition, betaine alleviated diet-induced disruption of hepatic lipid metabolism in mice, which was related to the modification of methylation on lipogenic genes [51].…”
Section: Discussionmentioning
confidence: 99%
“…The putative mechanisms underlying the effects of betaine on lipid metabolism included changes in gut microbiota (i.e., reductions in Intestinimonas, Acetatifactor, and Desulfovibrio, and increases in Lachnoclostridium and Romboutsia), with intergenerational metabolic impacts [49]. In addition, maternal betaine supplementation has been shown to reduce hepatic triglyceride content in offspring mice by decreasing the relative abundances of Proteobateria, Desulfovibrio, and Ruminococcus, but increasing Bacteroides and Parabacteroides [50]. In addition, betaine alleviated diet-induced disruption of hepatic lipid metabolism in mice, which was related to the modification of methylation on lipogenic genes [51].…”
Section: Discussionmentioning
confidence: 99%
“…Betaine is a growing biological methyl donor ( Bekdash, 2023 ). Betaine increases energy metabolism enzyme activity and reduces liver fat in hens ( Sun L et al, 2023 ). Betaine-supplemented hens have improved growth rate, feed efficiency, and carcass quality, especially during heat stress or disease outbreaks ( Suliman et al, 2023 ; Sun S et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota of infants born from obese mothers increased the susceptibility to NAFLD in the mice through fecal microbiota transplantation experiments (Soderborg et al, 2018). Our previous research also found that maternal HFD changed the distribution of gut microbiota and induced NAFLD in offspring mice (Sun et al, 2023). Bifidobacteria and Lactobacillus are recognized as beneficial microbiota in the gut.…”
Section: Introductionmentioning
confidence: 90%